2D layered perovskite containing functionalised benzothieno-benzothiophene molecules: formation, degradation, optical properties and photoconductivity. Issue 21 (1st May 2020) - Van Gompel, Wouter T. M.; Herckens, Roald; Denis, Paul-Henry; Mertens, Martijn; Gélvez-Rueda, María C.; Van Hecke, Kristof; Ruttens, Bart; D'Haen, Jan; Grozema, Ferdinand C.; Lutsen, Laurence; Vanderzande, Dirk
Abstract : Using a solvent vapour annealing method, the crystallinity and photoconductivity of a 2D perovskite containing functionalized benzothieno[3, 2- b ]benzothiophene cations was enhanced. Abstract : 2D layered hybrid perovskites are currently in the spotlight for applications such as solar cells, light-emitting diodes, transistors and photodetectors. The structural freedom of 2D layered perovskites allows for the incorporation of organic cations that can potentially possess properties contributing to the performance of the hybrid as a whole. In this study, we incorporated a benzothieno[3, 2- b ]benzothiophene (BTBT) alkylammonium cation into the organic layer of a 2D layered lead iodide perovskite. The formation and degradation of this material are discussed in detail. It is shown that the use of a solvent vapour annealing method significantly enhances the absorption, emission and crystallinity of films of this 2D layered perovskite as compared to regular thermal annealing. The photoconductivity of the films was determined using time-resolved microwave conductivity (TRMC) as well as in a device. In both cases, the solvent vapour annealed films show markedly higher photoconductivity than the films obtained using the regular thermal annealing approach.